Laparoscopic uterine isthmus anastomosis - Chen, Yili; Yang, Fan; Liu, Junxiu; Yao, Shuzhong (Fertility and sterility, 2025)
To demonstrate a laparoscopic surgical technique for reconstructing posttraumatic uterine isthmus separation in an adolescent patient, focusing on anatomical restoration and fertility preservation. Stepwise surgical video case report with narrated audio. A 16-year-old girl presented with oligomenorrhea and cyclic lower abdominal pain 1 year after a motor vehicle accident necessitating right lower limb amputation and partial pelvic resection. Transrectal ultrasound and computed tomography revealed complete separation between the uterine corpus and cervix at the isthmus level. Before the procedure, the patient was fully informed about the potential obstetric risks, including cervical incompetence, miscarriage, preterm birth, abnormal placentation, uterine rupture, and the possible need for a cesarean section. The laparoscopic procedure commenced with adhesiolysis to expose the isthmic discontinuity. A uterine manipulator was introduced transvaginally to delineate the cervical anatomy. After transection of the round ligaments, the uterine fundus was retroverted to expose the superior rupture margin referring to uterine anatomy and scar tissue position. Vasopressin is then injected into the myometrium to reduce bleeding during ultrasonic removal of scar tissue. Blunt and sharp dissection of the vesicouterine peritoneum, guided by the landmarks provided by the uterine manipulator, revealed the inferior rupture opening of the uterine isthmus. Eight interrupted sutures were performed in a full-thickness pattern, and luminal patency was confirmed intraoperatively using a Foley catheter inserted transvaginally. Then, continuous suture reinforcement was performed at the site of the uterine isthmic rupture, and the right round ligament was resutured to complete the reconstruction. The procedure concluded with peritoneal closure and placement of an abdominal drain. This study was approved by the Ethics Committee of The First Affiliated Hospital, Sun Yat-sen University ([2025]258). Restoration of uterocervical continuity, postoperative menstrual normalization, and preservation of fertility potential. The procedure was completed in 160 minutes with an estimated blood loss of 100 mL. Restoration of uterocervical continuity was immediately confirmed intraoperatively using a Foley catheter. There were no bladder or bowel injuries. The abdominal drain was removed on postoperative day 2, and the patient was discharged on postoperative day 5 after an uncomplicated recovery. The intrauterine Foley catheter was left in place for 10 days to maximize the reduction of risks associated with uterine isthmus wound dehiscence and uterine isthmus stenosis while minimizing the risk of intrauterine infection. Menstruation resumed in the month after surgery. The laparoscopic approach achieved successful anastomosis of the uterine isthmic rupture, restoring anatomical continuity between the uterine corpus and cervix. Postoperative assessment confirmed menstrual normalization and preservation of the patient’s fertility potential, with no surgical complications observed. The procedure’s minimally invasive nature provided magnified visualization critical for precise dissection and suture placement while minimizing adhesion formation compared with open techniques. These outcomes support the feasibility of laparoscopic uterine isthmic reconstruction in adolescents with posttraumatic isthmic separation, offering valuable insights for the surgical management of similar cases in the future. Anastomosis laparoscópica del istmo uterino Demostrar una técnica quirúrgica laparoscópica para la reconstrucción de una separación postraumática del istmo uterino en una paciente adolescente, enfocándose en la restauración anatómica y la preservación de la fertilidad. Reporte de un caso quirúrgico demonstrado paso a paso mediante el uso de video con narración de audio. Una adolescente de 16 años que se presentó con síntomas de oligomenorrea y dolor cíclico en la porción inferior del abdomen un año después de un accidente automovilístico que requirió la amputación de la extremidad inferior derecha y una resección pélvica parcial. La ecografía transrectal y la tomografía computarizada revelaron una separación completa entre el cuerpo y el cuello uterino a nivel del istmo. Antes del procedimiento, la paciente fue informada de los riesgos obstétricos potenciales, incluyendo incompetencia cervical, aborto espontáneo, parto prematuro, Desarrollo anormal de la placenta, ruptura uterina y la posible necesidad de cesárea. El procedimiento laparoscópico inició con la exposición de la discontinuidad en el istmo uterine mediante la lisis de adherencias. Un manipulador uterine introducido por via transvaginal fue utilizado para delinera la anatomía cervical. Luego de la transección de los ligamentos redondos, el fondo uterino fue retrovertido para exponer el margen superior de la ruptura, guiándose por la anatomía uterina y la posición del tejido fibroso. Luego se inyectó vasopresina en el miometrio para reducir el sangrado durante la extraccion bajo guia ecográfica del tejido fibroso. La disección roma y cortante del peritoneo vesicouterino, guiada por los puntos de referencia proporcionados por el manipulador uterino, reveló la abertura inferior de la ruptura del istmo uterino. Se realizaron ocho suturas interrumpidas de espesor completo y se confirmó la permeabilidad luminal intraoperatoriamente mediante un catéter de Foley introducido transvaginal. Luego se llevó a cabo una sutura continua de refuerzo en el sitio de la ruptura del istmo uterino, y el ligamento redondo derecho fue resuturado para completar la reconstrucción. El procedimiento concluyó con el cierre peritoneal y la colocación de un drenaje abdominal. Este estudio fue aprobado por el Comité de Ética del Primer Hospital Afiliado de la Universidad Sun Yat-sen ([2025]258). Restauración de la continuidad uterocervical, normalización menstrual postoperatoria y preservación del potencial de fertilidad. El procedimiento se completó en 160 minutos con una pérdida sanguínea estimada de 100 mL. La restauración de la continuidad uterocervical se confirmó inmediatamente durante la operación mediante un catéter de Foley. No hubo lesiones vesicales o intestinales. El drenaje abdominal fue retirado en el segundo día postoperatorio y la paciente egresó del hospital al quinto día postoperatorio tras una recuperación sin complicaciones. El catéter de Foley intrauterino fue dejado su lugar durante 10 días para maximizar la reducción del riesgo de dehiscencia de la herida del istmo uterino y de estenosis del istmo uterino, al mismo tiempo minimizando el riesgo de infección intrauterina. La menstruación se reanudó al mes de la cirugía. El abordaje laparoscópico logró una anastomosis éxitosa de la ruptura del istmo uterino, restaurando la continuidad anatómica entre el cuerpo uterino y el cervix. La evaluación postoperatoria confirmó la normalización menstrual y la preservación del potencial de fertilidad de la paciente, sin observarse complicaciones quirúrgicas. La naturaleza mínimamente invasiva del procedimiento permitió una visualización magnificada, la cual es crítica para la disección precisa y la colocación de suturas, minimizando la formación de adherencias en comparación con las técnicas abiertas. Estos resultados respaldan la viabilidad de la reconstrucción laparoscópica del istmo uterino en adolescentes con separación istmica postraumática, ofreciendo conocimientos valiosos para el manejo quirúrgico de casos similares en el futuro. [Display omitted]